Di-tri-octahedral smectite for the prevention of post-operative diarrhea in equids with surgical disease of the large intestine: Results of a randomized clinical trial - Hassel, Diana M. (2009)
The aim of this study was to evaluate the effects of a commercially available di-tri-octahedral (DTO) smectite product on clinical signs and prevalence of post-operative diarrhea in horses with colic associated with disease of the large intestine. Sixty-seven horses with surgical disease of the large intestine were randomly assigned to be treated with DTO smectite (n = 37; 0.5 kg via nasogastric intubation every 24 h for 3 days post-operatively) or a placebo (n = 30). The effect of treatment on fecal scores and clinical and hematological parameters, including heart rate, mucous membrane color, temperature, total white blood cell count, total neutrophil count and total plasma protein values, were determined. Horses treated with DTO smectite had a significant reduction in the prevalence of post-operative diarrhea (10.8%), compared with controls (41.4%). A significant improvement in mucous membrane color was observed 72 h post-operatively in horses receiving treatment, compared with placebo. Administration of DTO smectite to colic patients with disease of the large intestine reduced the occurrence of diarrhea in the early post-operative period.n = 37; 0.5 kg via nasogastric intubation every 24 h for 3 days post-operatively) or a placebo (n = 30). The effect of treatment on fecal scores and clinical and hematological parameters, including heart rate, mucous membrane color, temperature, total white blood cell count, total neutrophil count and total plasma protein values, were determined. Horses treated with DTO smectite had a significant reduction in the prevalence of post-operative diarrhea (10.8%), compared with controls (41.4%). A significant improvement in mucous membrane color was observed 72 h post-operatively in horses receiving treatment, compared with placebo. Administration of DTO smectite to colic patients with disease of the large intestine reduced the occurrence of diarrhea in the early post-operative period.n = 30). The effect of treatment on fecal scores and clinical and hematological parameters, including heart rate, mucous membrane color, temperature, total white blood cell count, total neutrophil count and total plasma protein values, were determined. Horses treated with DTO smectite had a significant reduction in the prevalence of post-operative diarrhea (10.8%), compared with controls (41.4%). A significant improvement in mucous membrane color was observed 72 h post-operatively in horses receiving treatment, compared with placebo. Administration of DTO smectite to colic patients with disease of the large intestine reduced the occurrence of diarrhea in the early post-operative period.